APC/C-Cdh1-targeted substrates as potential therapies for Alzheimer’s disease - Lapresa, Rebeca; Agulla, Jesus; Bolaños, Juan P.; Almeida, Angeles (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder and the main cause of dementia in the elderly. The disease has a high impact on individuals and their families and represents a growing public health and socio-economic burden. Despite this, there is no effective treatment options to cure or modify the disease progression, highlighting the need to identify new therapeutic targets. Synapse dysfunction and loss are early pathological features of AD, correlate with cognitive decline and proceed with neuronal death. In the last years, the E3 ubiquitin ligase anaphase promoting complex/cyclosome (APC/C) has emerged as a key regulator of synaptic plasticity and neuronal survival. To this end, the ligase binds Cdh1, its main activator in the brain. However, inactivation of the APC/C-Cdh1 complex triggers dendrite disruption, synapse loss and neurodegeneration, leading to memory and learning impairment. Interestingly, oligomerized amyloid-β (Aβ) peptide, which is involved in AD onset and progression, induces Cdh1 phosphorylation leading to APC/C-Cdh1 complex disassembly and inactivation. This causes the aberrant accumulation of several APC/C-Cdh1 targets in the damaged areas of AD brains, including Rock2 and Cyclin B1. Here we review the function of APC/C-Cdh1 dysregulation in the pathogenesis of AD, paying particular attention in the neurotoxicity induced by its molecular targets. Understanding the role of APC/C-Cdh1-targeted substrates in AD may be useful in the development of new effective disease-modifying treatments for this neurological disorder.